Representation of Liturgical Symbolic Meaning in the Temporary Worship Space of the St. Pius X Catholic Church, Karanganyar - Bonifacio Bayu Senasaputro; Riandy Tarigan; Fransiska Helena Putri (Jurnal Lingkungan Binaan Indonesia, 2026)
In the Catholic Church tradition, the worship space serves as a critical architectural framework for liturgical activities and for spatial articulations of symbolic meaning that structure ritual experience. Previous studies have predominantly addressed permanent church buildings, while investigations into temporary worship spaces remain limited, particularly in terms of their spatial adaptability and symbolic performance. This study aims to examine how the Pastoral Service Building, adapted as a temporary worship space at St. Pius X Catholic Church, Karanganyar, spatially represents liturgical symbolic meaning and constructs a sense of sacredness through architectural configuration. The research adopts a qualitative case study approach, employing direct observation of spatial geometry, circulation patterns, visual orientation, and lighting conditions during liturgical celebrations, complemented by in-depth interviews with the pastor, church administrators, and congregants. A semiotic framework is used to analyze and interpret spatial signs and architectural elements within the liturgical context. The findings show that despite physical constraints and the absence of permanent sacred elements, strategic spatial arrangement, such as geometry, circulation, congregation–altar orientation, sanctuary configuration, and lighting, preserves the symbolic structure of Catholic liturgy and supports a coherent ritual experience. The study offers insights into adaptive design strategies for temporary worship spaces, particularly in addressing spatial constraints while preserving symbolic and ritual functions.